Access to management and the informativeness of analyst research - Green, T. Clifton; Jame, Russell; Markov, Stanimir; Subasi, Musa (Journal of Financial Economics, 2014)
We examine whether access to management at broker-hosted investor conferences leads to more informative research by analysts. We find analyst recommendation changes have larger immediate price impacts when the analyst׳s firm has a conference-hosting relation with the company. The effect increases with hosting frequency and is strongest in the days following the conference. Conference-hosting brokers also issue more informative, accurate, and timely earnings forecasts than non-hosts. Our findings suggest that access to management remains an important source of analysts׳ informational advantage in the post-Regulation Fair Disclosure world.